Serum Pentraxin-3 as a Potential Biomarker for Early Detection of Diabetic Nephropathy in Type 2 Diabetes Mellitus: A Cross-Sectional Study - Noor Naji Khdher; Mutaz Sabah Ahmeid; Israa Hashim Saadoon; Alaa Abdullah Hassan (Academia Open, 2023)
This cross-sectional study aimed to assess the utility of serum Pentraxin-3 (PTX-3) as a biomarker for the early identification of diabetic nephropathy (DN) in patients with Type 2 Diabetes Mellitus (T2DM). A total of 90 participants, including 30 with T2DM and nephropathy, 30 with T2DM but without nephropathy, and 30 controls, were enrolled. Serum PTX-3 levels were measured, and correlations with clinical parameters were analyzed. The results revealed a significant elevation in serum PTX-3 levels in DN patients with T2DM. PTX-3 exhibited positive correlations with age, disease duration, blood urea, and serum creatinine, indicating its potential relevance to DN development and renal function. Conversely, non-significant negative correlations were observed with BMI and estimated glomerular filtration rate (eGFR). These findings suggest that serum PTX-3 could serve as a valuable biomarker for the early detection of diabetic nephropathy in Type 2 Diabetes Mellitus, potentially aiding in timely intervention and improved patient care. Highlights : Serum PTX-3 levels significantly elevated in Type 2 Diabetes patients with nephropathy, highlighting its potential as an early diagnostic biomarker. Positive correlations observed between PTX-3, age, disease duration, blood urea, and serum creatinine, suggesting its relevance to DN development and renal function. Serum PTX-3 holds promise for timely identification of diabetic nephropathy, facilitating improved patient care. Keywords : Diabetic Nephropathy, Pentraxin-3, Type 2 Diabetes, Biomarker. Early Detection